Future foods: Morphological scenarios to explore changes in the UK food system with implications for food safety across the food chain. (May 2023) - Garnett, Kenisha; Delgado, Joao; Lickorish, Fiona A.; Pollard, Simon J.T.; Medina-Vaya, Angel; Magan, Naresh; Leinster, Paul; Terry, Leon A.
Abstract: Scenarios are used to examine systemic change in food systems so policy makers can craft opportunities to improve the management of uncertainty and shape food policy. We present a number of alternative scenarios of the food system for 2035, developed with the Food Standards Agency, the independent government department working to protect public health and consumers' interest in relation to food for England, Wales and Northern Ireland. To build scenarios we employed morphological analysis; a non-quantified method for modelling multiple scenario variables (food system drivers, projections), simulating their interactions and all possible scenario combinations. A cross-consistency analysis compared all possible scenario combinations to identify which set of driver projections formed a logical (internally consistent) scenario. Recently, we augmented the scenarios to consider the potential impacts and consequences of Brexit and the pandemic on consumer food safety. Outputs illustrate the consequences of extreme impacts emerging from an optimistic (Global Trading) and pessimistic (Resource Tensions) future for the food system. The scenarios establish a context for foresight in decision-making and a framework for evaluating the robustness of policies considering the opportunities and challenges arising from Brexit and a global pandemic. Highlights: Morphological scenarios examine systemic change in food systems to address uncertainty. Scenario outputs reveal risks and opportunities related to change in food systems. Building capacity in scenario development helps to future-proof policy approaches. Scenarios establish links between foresight and the policy process.